2021
DOI: 10.6007/ijarbss/v11-i2/8430
|View full text |Cite
|
Sign up to set email alerts
|

Now Look What You’ve Done, COVID-19! The Impact on Academic Survival among Postgraduate Students in Malaysia

Abstract: The COVID-19 pandemic has led to the closure of various sectors in Malaysia including the education sector. The COVID-19 pandemic caused major concerns among postgraduate students. Little is known about the academic survival impacts of COVID-19 among tertiary students, especially among the postgraduates. Therefore, this article aims to identify the impact of COVID-19 pandemic on academic survival among postgraduate students in Malaysia. An online survey through Google Form is conducted in October 2020, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is perhaps at this time that the university must devote greater time to ensuring that these students receive psychological services, as well as social and financial support to mitigate the effects of personal losses, infection, loneliness, anxiety, and fears emanating from Covid-19 to ensure their academic success. Nasir et al (2021) suggest that universities launch an intervention using a digital platform, for instance, a chat box, which can connect them with the students at any time. This will allow students to pose any questions regarding their situation or highlight any problems they are confronted with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is perhaps at this time that the university must devote greater time to ensuring that these students receive psychological services, as well as social and financial support to mitigate the effects of personal losses, infection, loneliness, anxiety, and fears emanating from Covid-19 to ensure their academic success. Nasir et al (2021) suggest that universities launch an intervention using a digital platform, for instance, a chat box, which can connect them with the students at any time. This will allow students to pose any questions regarding their situation or highlight any problems they are confronted with.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, several studies have emerged related to the effects of Covid-19 on learning and mental-health well-being (Govender et al, 2021;Onwuegbuzie & Ojo, 2021;Osman & Keevy, 2021;Makhado et al, 2022;Mphahlele et al, 2021;Rwafa-Ponela et al, 2022). However, little exists in the literature on the experiences of postgraduate students (Nasir, Ramli & Som, 2021;King, 2022), particularly in the local context. The confusion, stress, and anxiety that emanated from various aspects of the pandemic would inevitably affect the research progress of many postgraduate research students, warranting a deeper understanding of the problems that this group of students faced.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that students had financial problems throughout the pandemic. A recent comprehensive study in Malaysia [29] found that students are under financial stress. Also, financial constraints are the leading cause of our country's poor college graduation rate, ranging between 18 and 20% for the last decade [30].…”
Section: "I Don't Have Enough Money To Meet My Educational Needs Such...mentioning
confidence: 99%